2016
DOI: 10.2485/jhtb.25.282
|View full text |Cite
|
Sign up to set email alerts
|

Human Amniotic Membrane Extracts have Anti-Inflammatory Effects on Damaged Human Corneal Epithelial Cells <i>In Vitro</i>

Abstract: The human amniotic membrane has therapeutic potential for several diseases such as cardiac ischemia, liver fibrosis, and ocular surface disorders. In the treatment of ocular surface disorders, human amniotic membrane transplantation promotes epithelial wound healing and suppresses inflammation. The objective of this study was to determine whether human amniotic membrane extracts (HAE) help damaged corneal epithelial cells recover from an inflammatory response. Human corneal epithelial cells (hCEC) which were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The anti-inflammatory mechanism of AM is not fully understood yet. In-vitro studies suggest that AM can inhibit expression of pro-inflammatory cytokines such as interleukin (IL) 1a, IL-1b [69] and IL-8 [70]. It contains immunomodulatory substrates, such as heavy chain (HC)-hyaluronan (HA)/pentraxin 3 (PTX3) in its matrix [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-inflammatory mechanism of AM is not fully understood yet. In-vitro studies suggest that AM can inhibit expression of pro-inflammatory cytokines such as interleukin (IL) 1a, IL-1b [69] and IL-8 [70]. It contains immunomodulatory substrates, such as heavy chain (HC)-hyaluronan (HA)/pentraxin 3 (PTX3) in its matrix [21].…”
Section: Discussionmentioning
confidence: 99%
“…The remnant has been reported to remain 3-10 weeks after cryopreserved AM transplantation in pemphigoid patient's eyes [13] and 9 weeks after transplantation of dry and cryopreserved AM in rabbit eyes [28,29]. On the other hand, the ability to induce apoptosis in inflammatory cells and subsequently reduce inflammation, or other anti-inflammatory mechanisms of AM [20,70,72,73], may compensate for certain types of inflammation to certain degrees. However, it becomes less effective when the inflammation is severe [1,19,21,26].…”
Section: Discussionmentioning
confidence: 99%
“…AME, an extract of the human amniotic membrane, has also been shown to have anti-inflammatory effects. From the experiment using human corneal epithelial cells, homogenized human AME less than 3 kDa had a greater capacity to decrease the inflammation and secretion of IL-6 and IL-8 [35]. Human AME has been proven to contain human neutrophil peptides, lysozyme, LL-37 (C-terminal part of the only human cathelicidin), bactericidal/permeability-increasing protein, calprotectin, and ubiquitin, and to show anti-inflammatory effects [36, 37].…”
Section: Discussionmentioning
confidence: 99%
“… Lee et al (2016) conducted a study to prove the anti-inflammatory effect of AME on human corneal epithelial cells (hCECs) and showed that it was a more efficient anti-inflammatory agent than negative control without inducing apoptosis. Besides, they attempted to identify which part of AME is responsible for this effect.…”
Section: Amniotic Membrane Extractmentioning
confidence: 99%